Media Digital Berbasis Android Dalam Pengujian Peserta Didik Di SMK Muhammadiyah Tanjung Redeb - Tarmidi Tarmidi*; Dian Hidayati; Nama Nama (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Android-based digital media in testing students at the Tanjung Redeb Muhammadiyah Vocational School is implement on a web-based or desktop basis, positively this test can increase the effectiveness of the time of educators and the accuracy of their corrections. However, there are frequent leaks of questions and answers, thus increasing fraud in its implementation. So that the awareness of educators is needed, as well as training that can increase the effectiveness of implementing the online exam.